Heritage weaving and memory policies in Chile. Ethnographic notes on “Patio 29” and “Villa San Luis” monuments in Santiago city (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The paper examines the link between patrimonial and public memory policies initiated in Chile in 1996. It critically explores the role of the process of turning something into heritage, inside the political management of the recent past. It’s undeniable that heritage protection of places used during the civic-military dictatorship (1973-1989) under the Law of National Monuments (17 288) has become a key piece in the public management of memory in Chile. However, it’s possible to observe that the heritage experiences as a whole also involves a series of disputes and dystopias that need to be elucidated. In this context, two paradigmatic experiences in Santiago de Chile, allow us to comprehend the rifts opened by heritage policies on memory public management. On the one hand, the General Cemetery’s “Patio 29” (Courtyard 29) with its detachments, both materials and symbolic; on the other, “Villa San Luis” (San Luis Villa), an icon of an urban dispute that put a strain on historical memory conservation. We pro- pose an ethnographic account that expresses and materializes those fissures caused by the tension between memory preservation duty and the abandonment and social oblivion of a past that’s politically and socially uncomfortable.
Keywords: Heritage; Memory Policies; Patio 29; Villa San Luis.